Sam Fox library orchestra folio No.1, 1st violin - MILES, Walter E. [et.al] (Sam Fox Pub., 1912)
SparkletsnBasket of RosesnEleanornValse DanseusenA garden dancenBowl of pansiesnAt sunsetnDancing leavesnWater liliesnMon plaisirnIn poppylandnDream of the flower